Three-stage periodic inventory system with decay and stochastic demand - Villacrusis, Baltazar P. (2011)
In this paper we study a three-stage inventory system to come up with an optimal periodic inventory policy. We formulate different models on a three-stage serial inventory system for a single-item and multi-item (both for with and without decay). In the formulation of all the models we consider a stochastic (e.g. normally distributed) demand. We use the concept of echelon stock to analyze the formulation of the models. The cost functions of some models are analyzed and programs were created to solve and generate numerical results for each model. All numerical results consider a normally distributed demand. We derive the single-stage model from a three-stage model.